Protection of Children's Rights After Divorce: Challenges and Solutions in Indonesian Law - Fiqi Syarifa (Alhurriyah, 2025)
The protection of children's rights during divorce is a constitutional mandate under Law Number 35 of 2014 on Child Protection. In Religious Courts, this protection is ideally safeguarded through the judge's ex officio rights, which allow them to rule beyond the parties' specific demands to serve the child's best interests. This research aims to comprehensively analyze the implementation of the judge's ex officio rights, specifically concerning rights to maintenance (nafkah), custody, identity, and participation in legal proceedings. Using a juridical-normative approach, this study examines the Indonesian legal framework, including the Child Protection Law, the Compilation of Islamic Law (KHI), and relevant Supreme Court regulations. The analysis indicates that although the legal foundation is substantial, the practical effectiveness of protecting children's rights remains suboptimal due to inconsistent regulations, low public legal awareness, and weak execution mechanisms. Consequently, the study proposes strategic recommendations to bridge this gap, including regulatory harmonization, reform of mediation procedures, increased judicial capacity, and the strengthening of judgment execution mechanisms to ensure the robust fulfillment of children's rights.